Constructing and maintaining family in the context of imprisonment - Jardine, Cara (The British journal of criminology, 2018)
For many families affected by imprisonment, the prison can become a central and damaging force in their lives. Yet, to fully understand the impact of imprisonment upon families, there is a need for greater critical engagement with the concept of the family, and how this is defined and operationalized. Utilizing Finch’s theory of family practices, this article will argue that the family relationships affected by imprisonment are not only highly individual, but also actively constructed through embodied displays of care and commitment. However, we must guard against privileging family displays that fit most comfortably within a white, middle-class framework, and ensure that the voices of all families affected by imprisonment are heard in the growing conversations about their needs.